Parkinsonian Neurotoxins Impair the Pro-inflammatory Response of Glial Cells - Rabaneda-Lombarte, Neus; Xicoy-Espaulella, Efren; Serratosa, Joan; Saura, Josep; Solà, Carme (Frontiers in Molecular Neuroscience, 2019)
Exposure to neurotoxic agents is a proposed risk factor for the development of neurological diseases. In the case of Parkinson’s disease (PD), epidemiological studies report that pesticide exposure is a risk factor for the pathology. It has been suggested that some chemical agents, such as rotenone and paraquat, that inhibit the mitochondrial respiratory chain (in the same way as the PD mimetic toxin 1-methyl-4-phenylpyridinium, MPP+) are involved in the development of PD. However, although the neurotoxic effect of such compounds has been widely reported using in vivo and in vitro experimental approaches, their direct effect on glial cells remains poorly characterized. In addition, to what extent these toxins interfere with the immune response of glial cells has also been underexplored. We used mouse primary mixed glial and microglial cultures to study the effect of MPP+ and rotenone on glial activation, in the absence and the presence of a pro-inflammatory stimulus (lipopolysaccharide plus interferon-γ, LPS+IFN-γ). We determined the mRNA expression of effector molecules that participate in the inflammatory response (pro-inflammatory cytokines and enzimes), as well as nitric oxide and cytokine production. We also studied the phagocytic activity of microglial cells. In addition, we evaluated metabolic changes associated with the observed effects, through the measurement of ATP production and the expression of genes involved in the control of metabolic pathways. We observed that MPP+ and rotenone did not induce per se any significant expression of pro-inflammatory markers by glial cells. However, the exposure of glial cultures to these neurotoxins, especially rotenone, impaired the pro-inflammatory response induced by LPS/IFN-γ. MPP+ and rotenone also impaired the phagocytic activity of microglial cells, and this effect was potentiated in the presence of LPS/IFN-γ. The deficit in ATP production that was detected, mainly in MPP+ and rotenone-treated mixed glial cultures, may be responsible for the effects observed. These results show that the response of glial cells to a pro-inflammatory challenge is altered in the presence of toxins inhibiting mitochondrial respiratory chain activity, suggesting that the glial immune response is impaired by such agents. This may have relevant consequences for brain function and CNS response to insults.